An Analysis of Cognitive Level in Reading Questions of English Textbook for Vocational High School - Andi Mega Januarti Putri; Rafiqa Rafiqa; Ainun Apriawan (Hasanuddin University, 2023)
The paper intends to analyze the cognitive level of questions from the text in the English Textbook. The researchers examined the cognitive level of the reading questions and the most dominant level in this book based on the levels of the revised edition of Bloom's Taxonomy. Because the information gathered was verbal, this study can be classified as a qualitative descriptive. The researchers used the textbook